The Development of Crello-assisted E-Modules to Train Critical Thinking Skills on Elasticity and Hooke's Law Material - Rahmayanti, Dinda; Risdianto, Eko; Hanisa Putri, Desy (Tadbir : Jurnal Studi Manajemen Pendidikan, 2023)
The research sought to determine the appropriateness and learners’ perceptions of the Crello-assisted E-Modules to Train Critical Thinking Skills on Elasticity and Hooke's Law Material. The research utilized the ADDIE (Analyse, Design, Development, Implementation, and Evaluation) development model. 1) The appropriateness results of the Crello-assisted E-Modules to Train Critical Thinking Skills on Elasticity and Hooke's Law Material had a mean percentage value of 87.67%; thus, it was in the Highly Appropriate category. 2) The findings of learners perceptions of e-modules were in the Excellent category, with a mean percentage value of 83.06%. Based on the validation and readability tests conducted on learners’ in High School/Islamic High School, the generated e-modules were extremely suitable for future use. The advantages of e-modules were that lies in their attractiveness, including can even be used anywhere and anytime, moreover could further build up learners’ critical thinking skills.